UPAYA PENINGKATAN KEBERSIHAN GIGI DAN MULUT PADA ANAK DISABLED CHILDRENDI SLB NEGERI TABANAN - Kencana, I Gede Surya; Artawa, I Made Budi (Poltekkes Kemenkes Denpasar, 2023)
The partner in this program is the head of the Tabanan Special School (SLB). The purpose of this community partnership program is to provide knowledge and self-development skills for disabled children (Special Needs) in dental health maintenance activities. This is based on the problems found, among others: 1) The knowledge of children with disabilities about self-development of dental and oral health is very lacking. 2) The skills of disabled children in brushing their teeth still have many mistakes. 3) The level of dental and oral hygiene of children with disabilities is included in the poor category. The solutions offered are conducting dental health education, checking students' oral and dental hygiene, improving tooth brushing skills by means of joint tooth brushing activities, and evaluating program applicability. The output produced in this partnership program is in the form of intellectual property rights in the form of a leaflet with the title: Efforts to Improve Dental and Oral Hygiene for disabled children at SLB Negeri Tabanan. The Target of Achievement is the Outcome of Scientific Publications in the Journal, give the ISSN/Proceedings of the Outcome Target: submitted.The program of health self-development activities, especially regarding the maintenance of dental and oral health for disabled children at the Tabanan State Special School, has not been implemented properly. The brushing skills of disabled children at SLB Negeri Tabanan are still in the category of needing guidance.